Smart integration of silicon nanowire arrays in all-silicon thermoelectric micro-nanogenerators. (30th June 2016) - Fonseca, Luis; Santos, Jose-Domingo; Roncaglia, Alberto; Narducci, Dario; Calaza, Carlos; Salleras, Marc; Donmez, Inci; Tarancon, Albert; Morata, Alex; Gadea, Gerard; Belsito, Luca; Zulian, Laura
Abstract: Micro and nanotechnologies are called to play a key role in the fabrication of small and low cost sensors with excellent performance enabling new continuous monitoring scenarios and distributed intelligence paradigms ( Internet of Things, Trillion Sensors ). Harvesting devices providing energy autonomy to those large numbers of microsensors will be essential. In those scenarios where waste heat sources are present, thermoelectricity will be the obvious choice. However, miniaturization of state of the art thermoelectric modules is not easy with the current technologies used for their fabrication. Micro and nanotechnologies offer an interesting alternative considering that silicon in nanowire form is a material with a promising thermoelectric figure of merit. This paper presents two approaches for the integration of large numbers of silicon nanowires in a cost-effective and practical way using only micromachining and thin-film processes compatible with silicon technologies. Both approaches lead to automated physical and electrical integration of medium-high density stacked arrays of crystalline or polycrystalline silicon nanowires with arbitrary length (tens to hundreds microns) and diameters below 100 nm.